Willingness to Pay for Social Health Insurance in Central Vietnam - Lan Hoang Nguyen; Anh Thuan Duc Hoang (Frontiers Media S.A., 2017)
BackgroundA social health insurance (SHI) program was implemented in Vietnam in 1992. Participation is compulsory for some groups, such as formal-sector workers and voluntary for other groups. In 2013, 68% of the total population was covered by SHI, with most enrollees from compulsory groups. Enrollment has remained low among persons whose enrollment is voluntary. As a result, households face financial risk due to high out-of-pocket payments for health care. The goal of this study is to identify willingness to pay (WTP) for the SHI scheme among persons whose enrollment is voluntary and to examine factors that influence their choice.MethodThree hundred thirty-one uninsured persons from three districts and one city of Thua Thien Hue province were interviewed face to face using a structured questionnaire. Contingent valuation technique was used to assess the WTP among the study participants. Each individual was asked to choose the maximum premium they were willing to pay for a health insurance card per year with three copayment levels of 0, 10, and 20%. Seven premium levels were offered ranging from 0 to 900,000 Vietnamese Dong (VND) (42.12 USD). The mean WTP of respondents for each scenario was estimated. Multiple linear regression analysis was used to identify factors influencing WTP for SHI.ResultsThe survey found that 73.1, 72.2, and 71.6%, respectively, for each copayment level, of the respondents would agree to participate in the SHI scheme and are willing to pay an annual premium of 578,926 VND (27.1 USD); 473,222 VND (22.1 USD); and 401,266 VND (18.8 USD) at the copayment levels of 0, 10, and 20%, respectively. The WTP for SHI is influenced by knowledge of SHI at all copayment levels (p value < 0.05). The more knowledge about SHI individuals have, the higher the WTP amount. Chronic disease was related to WTP only at a copayment level of 20% (p = 0.049).ConclusionEnhanced awareness of the benefits of SHI among the population should contribute to expanding SHI coverage in Vietnam.